1999
DOI: 10.1007/bf03161917
|View full text |Cite
|
Sign up to set email alerts
|

Performance of frequency-modulated pulses in NQR

Abstract: This paper presents an analysis of the performance of frequency-modulated pulses and of pulses modulated simultaneously in amplitude and frequency in the pure nuclear quadrupolar resonance (NQR) spectroscopy of spin 3/2 nuclei. Computer simulations are given of the offset compensation efficiency of such pulses as applied to single crystals. Spin evolution equations were solved numerically. Experimental measurements, using FM pulses, of the 35 C1 NQR of sodium chlorate (NaC1O3 ) single crystal and of mercuric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Theoretical and experimental investigations have suggested that shaped pulses suitable for NMR experiments can be readily applied to NQR experiments [66]. For instance, frequency modulated (FM) pulses have previously been applied in NQR experiments by Schurrer and Pérez [67]; however, these FM pulses possess a non-uniform ''zipper"-like excitation profile limited to distinct offset frequencies. Spectral ranges greater than 500 kHz can routinely be uniformly excited with WURST pulses [64,65,68], with excitation breadth limited by a combination of the resonance frequency and probe bandwidth, suggesting that WURST echo and WURST-QCPMG sequences may find use in NQR experiments for a variety of quadrupolar nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical and experimental investigations have suggested that shaped pulses suitable for NMR experiments can be readily applied to NQR experiments [66]. For instance, frequency modulated (FM) pulses have previously been applied in NQR experiments by Schurrer and Pérez [67]; however, these FM pulses possess a non-uniform ''zipper"-like excitation profile limited to distinct offset frequencies. Spectral ranges greater than 500 kHz can routinely be uniformly excited with WURST pulses [64,65,68], with excitation breadth limited by a combination of the resonance frequency and probe bandwidth, suggesting that WURST echo and WURST-QCPMG sequences may find use in NQR experiments for a variety of quadrupolar nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of frequency-modulated pulses have been calculated numerically for spin-3/2 nuclei, but not for higher order spins [22]. Here, we illustrate the principles and value of the theoretical approach outlined in Section 2 with a study of the transient NQR response of an I = 9/2 spin system to a shaped pulse.…”
Section: Transient Response To Modulated Rf Fieldsmentioning
confidence: 98%